2019
DOI: 10.13188/2325-4645.1000047
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Affecting Pregnancy Rate after Cervical Insemination of Dairy Ewes in Greece

Abstract: The objective of this study was to assess the factors affecting success of cervical Artificial Insemination (AI) with chilled semen in intensively reared dairy ewes in Greece. The study involved 1,785 adult ewes from 20 flocks of Lacaune and Chios sheep. A typical estrous synchronization protocol, including intravaginal placement of progestogen sponge for 14 days and injection of equine chorionic gonadotropin at sponge removal, was applied in ewes during mating period. All ewes were cervically inseminated 53-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…(31,32) On the other hand, the in vivo test depends largely on the fertility of the female, which is affected by a wide range of factors, such as farm, year, season, artificial insemination technique, and technician, (33) heat stress, (34)(35)(36) diet, (37) health status, as well as parity, lambing interval, body condition score, genetic traits, full functionality of reproductive organs, herd management, female prolificacy, nutritional management before and after artificial insemination, the type of estrus (natural or hormonally manipulated), and the site of deposition of the semen and climate factors. (38,39) On the other hand, the sperm parameters evaluated in this study were selected due to their predictive capacity in fertility. For instance, several studies have indicated that sperm viability (live/dead) is related to sheep fertility (40) and bull fertility (41)(42)(43)(44) after artificial insemination.…”
Section: Discussionmentioning
confidence: 99%
“…(31,32) On the other hand, the in vivo test depends largely on the fertility of the female, which is affected by a wide range of factors, such as farm, year, season, artificial insemination technique, and technician, (33) heat stress, (34)(35)(36) diet, (37) health status, as well as parity, lambing interval, body condition score, genetic traits, full functionality of reproductive organs, herd management, female prolificacy, nutritional management before and after artificial insemination, the type of estrus (natural or hormonally manipulated), and the site of deposition of the semen and climate factors. (38,39) On the other hand, the sperm parameters evaluated in this study were selected due to their predictive capacity in fertility. For instance, several studies have indicated that sperm viability (live/dead) is related to sheep fertility (40) and bull fertility (41)(42)(43)(44) after artificial insemination.…”
Section: Discussionmentioning
confidence: 99%